KNOWLEDGE LEVEL OF STROKE RISK FACTORS, SIGNS AND SYMPTOMS AMONG FAMILY OF PATIENT WITH STROKE AT RSUP DR. SARDJITO YOGYAKARTA - , ADIMAS ENDRO WIBISONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: In Indonesia, stroke is the third leading cause of death and also the country with the biggest number of the stroke patient in Asia. Knowledge relating stroke risk factors, signs and symptoms among family are one of the important things to be assessed as one of the reasons that contribute to the high number of the incidence. Objective: This study is aimed to determine and describe knowledge relating stroke risk factors, signs and symptoms among family of the patient with stroke at RSUP Dr Sardjito. Methods: a survey was conducted from 27th of January until 7th of February at Wijayakusuma outpatient clinic and Stroke unit ward of RSUP DR. Sardjito Yogyakarta. The subjects was family and relatives of patient with stroke, who attended Wijayakusuma outpatient clinic and Stroke Unit ward of RSUP DR. Sardjito Yogyakarta. The tools that has been used for interviewing subjects was questionnaire, that is modified and pretested. Result: Ninety-two subjects were interviewed during the study period. The subjects interviewed is aged range from 15 until 80. Nine sucjects of total 92 did not know a single risk factors of stroke while 14 of them did not know a single signs and symptoms of stroke. From univariate analysis, there were no significant relationship between each variables(age,sex, and educational level) against knowledge level of stroke risk factors, signs and symptoms(p>0.05). Conclusion: Based on the survey, the subjects know stroke risk factors, signs and symptoms overally. However, knowledge regarding certain risk factors, signs and symptoms of stroke are lacking. Considerable education is needed to increase the knowledge relating stroke risk factors, signs and symptoms in order to further promotion and prevention.